Teaching and learning practices for multimodal literacy in science education - Unsworth, Len; Tytler, Russell; Fenwick, Lisl; Humphrey, Sally; Chandler, Paul; Herrington, Michele; Pham, Lam (Multimodal Literacy in School Science, 2022)
In this chapter, we analyze pedagogic approaches that have centralized the role of literacy and multimodal disciplinary literacy in science. In the first section, we synthesize foundational approaches that foreground the role of literacy in scientific endeavour. This includes models informed by rhetorical theories and systemic functional linguistics, which have provided a metalanguage to make meanings visible as language patterns in supporting students from diverse socio-economic and linguistic backgrounds to understand and communicate intellectually challenging science content. The second section reviews studies that have foregrounded multimodal sense making in science, including a range of integrated approaches known as multimodal disciplinary literacy and representational construction approaches, which focus on mastery of the disciplinary-specific, representational languages of science subjects through guided inquiry. In the third section, we review recent transdisciplinary studies that have infused disciplinary multimodal literacy practices and strategies in science subjects and attend to developing teachers’ semiotic knowledge to explicitly scaffold multimodal texts as resources for building disciplinary knowledge. Our final section synthesizes our analysis of approaches to propose principles for designing a pedagogic framework for teachers of senior biology, chemistry and physics to mediate the literacy development and scientific knowledge construction of students from low socio-economic status backgrounds.